Pengaruh Terapi Peer Group terhadap Kepatuhan Diet Penderita Asamurat di Desa Mentor Kecamatan Sumberasih Kabupaten Probolinggo - Muhammad Dio Alfandi Wahid; Rizka Yunita; Nur Hamim (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Gout is an inflammatory arthritis caused by the accumulation of uric acid crystals. Dietary adherence is one of the managements of gout. The purpose of this study is to determine the influence of peer group therapy on the dietary adherence of gout sufferers in Mentor Village, Sumberasih District, Probolinggo Regency. This study uses a one-group pre-post test design (pre-experiment) research design. The total population was 36 respondents with gout, the sample studied was 33 respondents with gout using the Purposive Sampling technique, In accordance with the inclusion criteria willing to be a respondent, Permanent Resident of Mentor Village, Patients who have gout, Gout level value above seven point zero for men and Women more than six point zero Exclusion criteria Patients with comorbidities that interfere with the research (kidney, janttung, lung and so on), Patients do not participate in the entire activity or resign.Peer group therapy was carried out four times in 14 days. Statistical Test for dietary adherence using the Wilcoxon Test. The results of the study Before peer group therap was coalited, the Gout Diet Compliance value was moderate, 24 respondents (72.7%),while the after tritmen value of goud diet compliance of 31 respondents (93.9%), The results of the Wilcoxon statistical test,obtained p value = 0.000. This shows that Peer Group therapy affects dietary adherence of gout patients. Peer Group Therapy is a program that can be applied to gout patients who have low dietary adherence. Nurses are expected to be able to use Peer Group Therapy as a health promotion program.